Exploring the Role of Inquiry-Based Learning, Technology Integration, and Peer Mentoring in Developing Professional Competence of Educators in Indonesia - Sukini Sukini (Westscience Press, 2025)
This study assesses the combined effects of Inquiry-Based Learning, Technology Integration, and Peer Mentoring on educators' Professional Competence in Indonesia. In this quantitative study, a sample size of 86 respondents was drawn through simple random sampling. The research instrument was a structured questionnaire with a five-point Likert scale used for measuring perceptions about the variables. Data were analyzed using SPSS version 26, along with multiple linear regression. The results showed that all three independent variables significantly and positively predict Professional Competence, jointly accounting for 68.3% of the variance. Among these, inquiry-based learning had the strongest individual effect, followed by peer mentoring and technology integration. These findings support the integrated approach in professional development programs. This study offers valuable suggestions for policymakers and educational stakeholders to further improve the professional competencies of teachers, leading to a better quality of education in Indonesia.